Oceanic thermal structure mediates dive sequences in a foraging seabird. Issue 13 (24th May 2020) - Meyer, Xavier; MacIntosh, Andrew J. J.; Chiaradia, Andre; Kato, Akiko; Ramírez, Francisco; Sueur, Cédric; Ropert‐Coudert, Yan
Abstract: Changes in marine ecosystems are easier to detect in upper‐level predators, like seabirds, which integrate trophic interactions throughout the food web. Here, we examined whether diving parameters and complexity in the temporal organization of diving behavior of little penguins ( Eudyptula minor ) are influenced by sea surface temperature (SST), water stratification, and wind speed—three oceanographic features influencing prey abundance and distribution in the water column. Using fractal time series analysis, we found that foraging complexity, expressed as the degree of long‐range correlations or memory in the dive series, was associated with SST and water stratification throughout the breeding season, but not with wind speed. Little penguins foraging in warmer/more‐stratified waters exhibited greater determinism (memory) in foraging sequences, likely as a response to prey aggregations near the thermocline. They also showed higher foraging efficiency, performed more dives and dove to shallower depths than those foraging in colder/less‐stratified waters. Reductions in the long‐term memory of dive sequences, or in other words increases in behavioral stochasticity, may suggest different strategies concerning the exploration–exploitation trade‐off under contrasting environmental conditions. Abstract : Little penguins foraging in warmer/more‐stratified waters exhibited less stochastic foraging sequences likely as a response to prey aggregations nearby the thermocline. Ultimately, they showed higher foraging efficiency and numbers of dives, and lower mean dive depths than those foraging in colder/less‐stratified waters.